2014
DOI: 10.3390/cancers6031570
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Expression of Cancer Stem Cell-Like Properties and Cancer-Associated Fibroblast-Like Properties in a Primary Culture of Breast Cancer Cells

Abstract: The importance of cancer-associated fibroblasts (CAFs) in cancer biology has been recently highlighted owing to their critical roles in cancer growth, progression, metastasis, and therapeutic resistance. We have previously established a primary culture of breast cancer cells, which showed epithelial-mesenchymal transition and cancer stem cell-like properties. In this study, we found that the primary culture also showed CAF-like properties. For example, hypoxia inducible factor 1α (HIF1A) and its downstream gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Ishikawa et al. found that many enzymes involved in glycolysis, such as GAPDH, LDH, PGAM1, and PKM2, were highly overexpressed in breast cancer cells. A reduction in the nutrient supply can lead to cell death by ATP depletion, if cell proliferation is not limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishikawa et al. found that many enzymes involved in glycolysis, such as GAPDH, LDH, PGAM1, and PKM2, were highly overexpressed in breast cancer cells. A reduction in the nutrient supply can lead to cell death by ATP depletion, if cell proliferation is not limited.…”
Section: Discussionmentioning
confidence: 99%
“…And it has been demonstrated that cell proliferation is a process that consumes large amounts of energy [25], then up-regulated GAPDH can participate in processing more energy. Ishikawa et al [26] found that many enzymes Figure 8. Knockdown of GAPDH reduced tumorigenicity of NCI-H520 cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is presently unclear whether MSC-cancer cell communication occurs before or as a consequence of tumor stroma activation or if both occur simultaneously as a result of hypoxia. Nonetheless, one of the first steps in metastasis influenced by these soluble factors secreted from tumor stroma involves a change in the cancer cells from an epithelial phenotype to a mesenchymal phenotype, a process known as epithelial-mesenchymal transition (EMT), which confers the ability to invade and metastasize, and promotes stem cell-like properties [23].…”
mentioning
confidence: 99%
“…Foregoing investigations have revealed PGAM1 overexpression in several cancers such as clear cell renal carcinoma (CCRC), glioma, oral squamous cell carcinoma (OSCC), breast cancer, human nonsmall lung cancer, pancreatic ductal adenocarcinoma, prostate cancer, colorectal cancer, hepatocellular carcinoma, and urothelial bladder cancer ( Table and Figure ).…”
Section: Overexpression Of Pgam1 In Various Cancersmentioning
confidence: 99%
“…27 Thus, PGAM1 has potential ability to derive the metastasis in a metabolic independent way. 31 breast cancer, 32 human nonsmall lung cancer, 33 pancreatic ductal adenocarcinoma, 34 prostate cancer, 35 colorectal cancer, 36 hepatocellular carcinoma, 14 and urothelial bladder cancer 37 ( Table 2 and Figure 3). In the hypoxia tumor microenvironment, cancer cells are oxygen independent for energy production.…”
Section: Nonmetabolic Functions Of Pgam1mentioning
confidence: 99%